Selected Topics in Group IV and II-VI Semiconductors : Proceedings of Symposium L and Symposium D of the 1995 E-Mrs Spring Conference, Strasbourg, France, 22-26 May 1995 - Kasper, E. (European Materials Research Society symposia proceedings., 1996)
This book contains the proceedings of two symposia which brought together crystal growers, chemists and physicists from across the world. The first part is concerned with silicon molecular beam epitaxy and presents an overview of the most research being done in the field. Part two discusses the problems dealing with purification, doping and defects of II-VI materials, mainly of the important semiconductors CdTe and ZnSe. The focus is on materials science issues which are the key for a better understanding of these materials and for any industrial application.